Post-Blunt Traumatic Hemobilia From Pseudoaneurysm Successfully Treated With Embolization - Hong Duc, Pham (Cureus, 2020)
Hemobilia is an uncommon but serious complication of traumatic liver injury. Diagnosis can be difficult because the presentation of gastrointestinal (GI) bleeding may be minimal or massive, and its delay is quite variable, ranging from a few days to several months. Radiologic evaluation, including ultrasound, CT, endoscopic retrograde cholangiopancreatography, and angiography, can be used for the diagnosis. Once the clinical presentation and diagnosis are considered, diagnostic and therapeutic arteriography must be performed as soon as possible. Here, we present a case of hemobilia two weeks postoperative for blunt traumatic liver injury in a 13-year-old boy who was treated successfully by N-butyl 2-cyanoacrylate (NBCA) embolization of the pseudoaneurysm.